Systematic Literature Review: Integrating Human Resource Management (HRM), Human Resource Development (HRD), and Industrial Relations (IR) in Fostering Sustainable Organizational Performance - Ananta, Shahrul Dwi; Ashari, Regita Niken; Murwani, Fulgentius Danardana; Wardana, Ludi Wishnu; Osiyo, Immanuel Ustradi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The advancement of industry and technology requires companies to possess competent human resources to support sustainable growth. This study employs a Systematic Literature Review (SLR) method to identify, evaluate, and interpret all relevant studies on the topic. The objective of this research is to explore the roles of HRD, HRM, and IR in building sustainable organizational performance. The findings indicate that the integration of HRM, HRD, and IR forms a strategic foundation for sustainable organizational performance. HRM provides strategic direction and innovation, HRD develops competencies and adaptability, while IR ensures social stability and productivity. The synergy among these three functions results in organizations that are competitive, resilient, and sustainable, where sustainability is supported by high-quality human resource governance. The findings suggest that integrating HRM, HRD, and IR has the potential to serve as a human resource management model that supports operational efficiency, social sustainability, innovation, and long-term organizational competitiveness, warranting further implementation and research.